The Effect of Dietary Protein and Energy Levels During the Growing Period of Egg-type Pullets on Internal Egg Characteristics of Phase One of Production in Arid Hot Climate - Babiker, M.S.; Abbas, S.A.; Kijora, C.; Danier, J. (International Journal of Poultry Science, 2011)
A (3 x 3) factorial arrangement was used in a completely randomized design to study the effect of protein and energy levels during the growing period of pullet on subsequent egg production performance. Three levels of protein and three levels of energy during stages of pullet growth (starter 0 to 6 wk, grower 7 to 12 wk and developer 13 to 18 wk of age) and their effect on laying performance (22 to 36 wk of age) were evaluated. In all phases of growing period, control levels of protein (P1) and energy (E1) were set according to NRC (1994) and the other levels were higher (P2 and E2) and (P3 and E3). A total of 9 treatments in each phase of the growth period were employed (P1 = 18, P2 = 20 and P3 = 22% CP) and (E1 = 3000, E2 = 3100 and E3 = 3200 kcal of ME/kg of diet) starter, (P1 = 16%, P2 = 18% and P3 = 20% CP) and (E1 = 3000, E2 = 3100 and E3 = 3200 kcal of ME/kg of diet) grower and (P1 = 15%, P2 = 17% and P3 = 19% CP) and (E1 = 3050, E2 = 3150 and E3 = 3250 kcal of ME/kg of diet) developer. Each treatment was replicated three times with ten birds each. Treatments in the factorial arrangement were kept the same for bird groups in every phase but at 19 week of age all groups were shifted to the layer diet up to the end of the trial. The layer performance of the different treatment groups was evaluated. In phase one of egg production cycle (22 to 36 week of age), egg mass was significantly (p